Bio-cement and bio-cementation - Shah Rizan Shahdan. (2010)
Construction on marine clay has proven to be a challenging task as this soil has a tendency to undergo liquefaction under a range of stress, thereby causing landslides in extreme cases. This is alarming as Singapore has extensive land reclamation along its coastal areas. Currently this is done using cement columns mixed in situ at relevant sites. This is a cause of environmental concern due to the large amount of CO2 generated by the production of cement. This project aims to address both issues by adopting novel environmentally friendly approaches to strengthen the marine clay. The project explores the viability of several chemical based methods of strengthening using these components: addition of aluminum oxide (Al2O3), precipitation of calcium carbonate (CaCO3), precipitation of ferrous hydroxide (FeOH3) and precipitation of ferrous sulfide linkages (FeS). The project also explores microbial possibilities of strengthening clay, using urease producing bacteria (UPB) and sulfate reducing bacteria (SRB). Using these processes in the laboratory, strength up to 496 kPa (UCS) was achieved. A matrix of precipitation of ferrous hydroxide (FeOH3) with ferrous sulfide linkages (FeS) showed the most potential for further studies, with an increase of compressive strength from 60 kPa to 450 kPa. Generally, compressive strength in all experiments increases up to 5 folds. Based on the preliminary results, the methods explored in this project are determined to be promising for cost-effective and efficient soft marine clay improvement with a wide range of potential applications. This report is relevant to all those involved in the use of industrial byproducts to improve soil and geotechnical properties. This is Part 2 of the EN63 Final Year Project Report. For content not listed in this document, please refer to Part 1, submitted by Liao Jianting.